Evaluation of occlusal pattern in periodontitis patients using T-scan analysis - B A Deepika; Jaiganesh Ramamurthy (Wolters Kluwer Medknow Publications, 2022)
Occlusal analysis is important to analyze any disharmony in occlusion. Atraumatic dental occlusion leads to evolution of T-scan. T-scan gives a valuable procedure for clinical assessment and perception of occlusal problems. T-scan can also be used in periodontitis patients for checking the occlusal pattern. Occlusal problems and periodontal disease relationship remains controversial. Further research is needed to determine whether occlusal adjustment is necessary for periodontal treatment. The main aim of the study was to assess the occlusal pattern using T-scan in periodontitis patients. Thirty periodontitis subjects were taken and checked for occlusion using T-scan. The subject's age group was 35-55 years. The study included 15 males and 15 females. Plaque index, gingival index, attachment loss, probing depth, centric occlusion (CO), protrusion, right lateral, and left lateral were the parameters studied. Occlusal adjustments were needed to decrease and dissipate the abnormal occlusal forces. The significance of statistical tests for various movements are as follows: CO (right and left) (P = 0.077) P > 0.05; protrusion (right and left) (P = 0.09) P > 0.05; left side lateral (right side and left side) (P = 0.01) P < 0.05; right lateral (right side and left side) (P = 0.00) P < 0.05. CO and protrusion (right, left) for males and females are not significant. Left lateral and right lateral (right, left) for males and females were significant. The T-scan manages adequate specificity and sensitivity. Hence, these act as a distinctive tool for diagnosis and better unreliable when used intraorally. The T-scan method is definitely a valuable tool for examining and evaluating the occlusal contacts during maximal intercuspation.